Characterization of the prostaglandin E2 sensitive (EP)-receptor in the rat isolated trachea. - Lydford, S. J. (1994)
1. Using a range of natural and synthetic prostanoid receptor agonists and antagonists, we have shown that the rat isolated trachea contains a heterogeneous population of prostaglandin receptor sub-types mediating both relaxation and contraction of the smooth muscle. Prostaglandin E2 (PGE2) elicits smooth muscle relaxation of pre-contracted preparations, the responses being well defined, with a mean potency (p[A50]) of 7.81 +/- 0.05. 2. 11-deoxy PGE1 16,16-dimethyl PGE2 and misoprostol were all full agonists at this receptor, whilst AH13205 was a low potency agonist, and sulprostone was inactive. 3. The EP1 receptor antagonist, AH6809 (5 microM), and the selective DP receptor antagonist, BW A868C (0.1 microM), had no significant effect on the concentration-effect (E/[A]) curves to PGE2. 4. The putative EP4-receptor antagonist, AH23848B, produced non-competitive antagonism of the PGE2 response curves; pA2 values of 5.07 +/- 0.15 and 5.24 +/- 0.19 were obtained at concentrations of 30 microM and 100 microM respectively. 5. The synthetic thromboxane A2 mimetic, U46619, caused smooth muscle contractions, with a mean p[A50] of 6.90 +/- 0.11. This response was antagonized by the TP receptor antagonist, GR32191B, yielding a mean pA2 of 8.31. 6. At concentrations of 1 microM and above, prostaglandin D2 (PGD2) and the IP-receptor agonist, cicaprost, generally elicited concentration-dependent relaxations of the rat trachea. Prostaglandin F2 alpha (PGF2 alpha) was without affinity or efficacy. 7. These data suggest that the rat isolated trachea contains EP-receptors, TP-receptors, and few, if any DP, IP or FP-receptors.(ABSTRACT TRUNCATED AT 250 WORDS)